Vermicomposting of cow manure: Effect of time on earthworm biomass and chemical, physical, and biological properties of vermicompost. (February 2022) - Ferraz Ramos, Rodrigo; Almeida Santana, Natielo; de Andrade, Nariane; Scheffer Romagna, Izabelle; Tirloni, Bárbara; de Oliveira Silveira, Andressa; Domínguez, Jorge; Josemar Seminoti Jacques, Rodrigo
Graphical abstract: Highlights: Forty-four variables were evaluated during 120 days of vermicomposting. The first 45 days characterized the initial vermicomposting phase. The largest physical–chemical changes occurred in the final phase. At least 120 days are required to produce earthworm matrices. The dissolved organic matter aromaticity was modified by vermicomposting. Abstract: Vermicomposting is a biological process for efficient cattle manure treatment, but the vermicomposting time determines the quality of the vermicompost. The objective of this study was to evaluate the effect of cattle manure vermicomposting time on earthworm biomass and the changes in physical, chemical, and biological in properties of the vermicompost. The cattle manure was inoculated with Eisenia andrei earthworms and conducted vermicomposting for 0, 15, 30, 45, 60, and 120 days. The analysis of 44 chemical, physical, and biological properties allowed the vermicomposting process to be divided into initial (<45 days) and final (45–120 days) phases. The initial phase was characterized by high microbial activity and the final by high physical–chemical transformation of the vermicompost and an increase in earthworm density. The organic matter aromaticity increased until the 45th day, subsequently decreasing. Although 30 d of vermicompost are sufficient to obtain a high-quality organic fertilizer, 120 d are necessary for producing matrices.